Advanced control of electrical machine systems - Zhou, Jianying. (2008)
This thesis presents the results on advanced control of electrical machine systems. In particular, nonlinear robust control for a class of electrical machine systems and dedicated control for hard disk drive servos are studied. In the first part of the thesis, the emphasis is on establishing nonlinear robust control frameworks for as a class of electrical machine systems.